Lymphocyte Subset Alterations Associated with Increased Spontaneous Lymphocyte Proliferation in Human T Lymphotropic Virus (HTLV) Infection: Distinctive Patterns for HTLV-I versus HTLV-II Infection - Prince, Harry E.; Golding, JonelIe; York, Joanne (The Journal of infectious diseases, 1994)
We determined if the association between SLP-positive status and lymphocyte subset alterations characteristic of HTLV-II infection also characterizes HTLV-I infection. The study included HTLV-infected and control subjects from the Los Angeles area who are participants in the Retroviral Epidemiology in Donors Study sponsored by the National Heart, Lung and Blood Institute. Lymphocyte subsets were assessed by two-color flow cytometric analysis of lysed whole blood samples as previously described. The monoclonal antibody combinations included anti-CD4 or anti-CD8 paired with anti-HLA-DR, anti-CD45RA, or anti-CD45RO. In support of our earlier findings, the SLP-positive HTLV-II-positive group showed significantly higher absolute levels of lymphocytes and CD4 and CD8 cells compared with the control group. Although the proportions of HLA-DR-positive CD4 cells in the control and SLP-positive HTLV-II-positive groups were similar to values in the previous study, the difference was not statistically significant. In contrast, the differences in the proportions of CD45RA-positive and CD45RO-positive CD4 cells did reach statistical significance in this comparison of the SLP-positive HTLV-II-positive group and the control group. Further, values for the SLP-positive HTLV-II-positive group were significantly different from those of the SLP-negative HTLV-II-positive group. Also in support of our earlier findings, the proportions of HLA-DR-positive CD8 cells and CD45RA-positive CD45RO-positive CD8 cells were significantly different in the SLP-positive HTLV-II-positive group compared with the control and SLP-negative HTLV-II-positive groups. As previously observed, none of the parameters measured were significantly different in the SLP-negative HTLV-II-positive group versus the control group.